Attention‐deficit/hyperactivity disorder is associated with increased risk of cardiovascular diseases: A systematic review and meta‐analysis - Li, Lin; Yao, Honghui; Zhang, Le; Garcia‐Argibay, Miguel; Du Rietz, Ebba; Brikell, Isabell; Solmi, Marco; Cortese, Samuele; Ramos‐Quiroga, J. Antoni; Ribasés, Marta; Chang, Zheng; Larsson, Henrik (JCPP advances, 2023)
Attention‐deficit/hyperactivity disorder (ADHD) often co‐occurs with other psychiatric and physical diseases. However, available evidence on associations between ADHD and cardiovascular diseases (CVDs) is mixed. To systematically review, quantitatively synthesize, and appraise available evidence on the link between ADHD with CVDs, we searched relevant articles in PubMed, Embase, PsycINFO, and Web of Science from inception to May 1, 2022. Study quality was assessed by using the Newcastle‐Ottawa Scale, and random‐effects model meta‐analyses were performed. A total of 18,391,169 (ADHD: n = 421,224) individuals from 11 studies were included in our systematic review and 8,196,648 (ADHD = 332,619) individuals from five studies were included in the main meta‐analysis of adjusted estimates. Pooled estimates showed that ADHD was significantly associated with an increased risk of CVDs in analyses based on adjusted effect size (odds ratio (OR) = 1.96; 95% confidence interval (CI) = 1.19–2.23, Q = 140.74, P Q < 0.001, I 2 = 97.2%). When restricted among adults, the heterogeneity declined to null (OR = 1.73; 95% CI = 1.14–2.62, Q = 6.28, P Q = 0.10, I 2 = 6.28%), suggesting age might be the main source of heterogeneity. In subgroup analyses, we found increased risk of CVDs associated with ADHD across age groups, type of CVDs, and data sources. This systematic review and meta‐analyses indicate that ADHD is associated with increased risk for CVDs, but further studies with various study designs are warranted to advance the understanding of the underlying mechanisms for the observed association between ADHD and CVDs. Additional research is also needed to resolve the role of ADHD medications which remains unclear due to the limited number of primary studies exploring this issue.